Evolutive Study of Dietary Aspects and Intestinal Microbiota of Pediatric Cohort with Cow's Milk Protein Allergy - Ana M. Castro; Sandra Navarro; Ignacio Carvajal; Agueda García; Marta Suárez; Paula Toyos; Silvia Rodríguez; Santiago Jimenez; David González; Cristina Molinos; David Pérez-Solís; Porifirio Fernández; et al. (MDPI AG, 2024)
Background: One of the most common food allergies in the pediatric population is allergy to cow's milk protein (CMPA). Treatment consists of avoiding cow's milk proteins in lactating mothers and/or using therapeutic formulas based on hydrolysates or vegetable formulas. In infants with CMPA at diagnosis, a different gut microbial profile has been found compared to healthy children, with a reduction in beneficial bacteria. The aim of this study was to evaluate changes in the gut microbiota profile and its metabolites, dietary patterns and anthropometric variables in a pediatric cohort with CMPA after six months on a restrictive diet compared to healthy controls. Methods: In total, 21 patients diagnosed with CMPA and a control group of 24 healthy infants participated in this study. The fecal microbiota of all participants were investigated by metataxonomic analysis of 16S rDNA amplicons, and fecal short-chain fatty acids were measured by gas chromatography. Epidemiological assessment and dietary questionnaires were carried out for both groups. Results: Regarding growth, no significant differences were found, but differences in dietary intake of some macro- and micronutrients were observed. Patients who were breastfed at six months had higher bifidobacteria and lipid intakes than patients fed with hydrolyzed formulas. Conclusions: Although the growth of CMPA infants fed with therapeutic formula is similar to breastfed CMPA infants, there are differences in microbiota composition and macronutrient intake that underline the importance of continued breastfeeding in CMPA cases.